In‐situ follicular neoplasia: a clinicopathological spectrum. Issue 6 (22nd September 2021) - Tamber, Gurdip S; Chévarie‐Davis, Myriam; Warner, Margaret; Séguin, Chantal; Caron, Carole; Michel, René P
Abstract : Aims: In‐situ follicular neoplasia (ISFN) occurs in approximately 2–3% of reactive lymph nodes, and is currently set apart from 'partial involvement by follicular lymphoma' (PFL). ISFN can progress to overt lymphoma, but precise parameters with which to assess this risk and its association with related diseases remain incompletely understood. The aim of this study was to explore these parameters. Methods and results: We reviewed 11 cases of ISFN and one of PFL between 2003 and 2018. Ten patients had ISFN in the lymph nodes, and one had ISFN in the spleen. Haematoxylin and eosin and immunohistochemical stains were reviewed. Involvement of follicles by ISFN was scored with a three‐tier scheme. Of five patients with low ISFN scores, one had chronic myelomonocytic leukaemia, one had mycosis fungoides, and three were free of haematopoietic disease. Among them, four are alive and one was lost to follow‐up. Of the six ISFN patients with high scores, two had concurrent marginal zone lymphomas, one had concurrent diffuse large B‐cell lymphoma (DLBCL), one had Castleman‐like disease, one had progressive transformation of germinal centres with IgG4‐related disease, and one had no haematopoietic disease; all are alive except for one who died of concurrent DLBCL. The patient with PFL developed DLBCL 7 years after diagnosis. Conclusions: On the basis of this limited series, we conclude that only cases with high scores are associated with an overt lymphoma or an abnormal lymphoid process, and that scoring may be a useful parameter with which to assess the risk of associated lymphoma, and deserves further study. We also performed a comprehensive review of the literature. Abstract :